2019
DOI: 10.1002/jmri.26664
|View full text |Cite
|
Sign up to set email alerts
|

3D‐T prepared zero echo time‐based PETRA sequence for in vivo biexponential relaxation mapping of semisolid short‐T2 tissues at 3 T

Abstract: Background: In addition to the articular cartilage, osteoarthritis (OA) affects several other tissues such as tendons, ligaments, and subchondral bone. T1ρ relaxation study of these short T2 tissues may provide a more comprehensive evaluation of OA. Purpose: To develop a 3D spin-lattice relaxation in the rotating frame (T1ρ) prepared zero echo time (ZTE)-based pointwise encoding time reduction with radial acquisition (3D-T1ρ-PETRA) sequence for relaxation mapping of semisolid short-T2 tissues on a clinical 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
0
6
1
Order By: Relevance
“…Similarly, Liu et al [25], Jang et al [39], and Liu et al [38] employed UTE T2* quantification to show that the patellar tendon had a short T2* fraction of 75-85%. Our study showed different values than Sharafi et al, who found a T1ρ short fraction of ~47% [32]. Possible reasons for this could be differences in the acquisition techniques (e.g., PETRA versus UTE), different vendor platforms, different TSLs, differences between living and postmortem tissues, and subject variability.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…Similarly, Liu et al [25], Jang et al [39], and Liu et al [38] employed UTE T2* quantification to show that the patellar tendon had a short T2* fraction of 75-85%. Our study showed different values than Sharafi et al, who found a T1ρ short fraction of ~47% [32]. Possible reasons for this could be differences in the acquisition techniques (e.g., PETRA versus UTE), different vendor platforms, different TSLs, differences between living and postmortem tissues, and subject variability.…”
Section: Discussioncontrasting
confidence: 88%
“…For example, a 3D cartesian turbo flash sequence has been used for data acquisition with a T1ρ preparation module consisting of a spin-lock pulse divided into four segments with an alternating phase [19][20][21]. However, there appears to be only one study on the bicomponent analysis of T1ρ in the tendon, which used a pointwise encoding time reduction with radial acquisition (PETRA) sequence [32].…”
Section: Introductionmentioning
confidence: 99%
“…Even though the minimum TE of the sequence, that is, 5.8 ms (limited by the device hardware and sequence implementation), was used in this study, the TE may not be short enough to preserve the signals from all short T 1 ρ components. An ultra‐short TE sequence may improve performance in biexponential T 1 ρ mapping, especially for short T 1 ρ components . In addition, the Hankel matrix has been proposed to enhance the low rankness of the image matrix in accelerated MRI.…”
Section: Discussionmentioning
confidence: 99%
“…An ultra-short TE sequence may improve performance in biexponential T 1ρ mapping, especially for short T 1ρ components. 49 In addition, the Hankel matrix [50][51][52] has been proposed to enhance the low rankness of the image matrix in accelerated MRI. It can also be used as an additional constraint to further improve the reconstruction performance of Bio-SCOPE and will be investigated in our future work.…”
Section: Discussionmentioning
confidence: 99%
“…Sharafi et al developed a 3D-T1ρ zero echo time (ZTE) based sequence with pointwise encoding time reduction with radial acquisition (PETRA) for biexponential relaxation mapping of knee tissues including patellar tendon and Achilles tendon. They were able to successfully demonstrate the feasibility of the sequence for bicomponent T1ρ assessment of these tissues (67). In this study, we reviewed various studies utilizing UTE sequences for tendon imaging, examining their results, advantages, and drawbacks.…”
Section: Ute T1ρmentioning
confidence: 99%